A PROJECT FINANCING SYSTEM BASED ON PUBLIC OPINION AND THE ASSOCIATED FINANCIAL RISKS - Madinabonu Khasanbayevna Abdullayeva; Zаrnigоr Kоmоl qizi Murtоzаevа (Modern American Journals, 2025)
In this article, one of the priorities of the reforms carried out in our country to ensure the openness and transparency of the budget system, that is, to ensure the active participation of citizens in determining the directions of expenses carried out from the local budget of the relevant territory. It is also covered by the project financing system, which is formed on the basis of public opinion, introduced for this purpose, and the financial risks that may arise in it.
Keywords: Public opinion, project, mechanism, citizen, process, financing system, local authorities, legislation, financial risks.